The micro potential for social change: Emotion, consciousness, and social movement formation - Summers-Effler, Erika (Sociological Theory, 2002)
Can one explain both the resilience of the status quo and the possibility for resistance from a subordinate position? This paper aims to resolve these seemingly incompatible perspectives. By extending Randall Collins’s interaction ritual theory, and synthesizing it with Norbert Wiley’s model of the self, this paper suggests how the emotional dynam- ics between people and within the self can explain social inertia as well as the possibility for resistance and change. Diverging from literature on the sociology of emotions that has been concerned with individual emotional processes, this paper considers the collective level in order to explore how movement action is motivated. The emotional dynamics of subordinate positioning that limit women’s options in face-to-face inter- actions are examined, as are the social processes of developing feminist consciousness and a willingness to participate in resistance work. Pointing toward empirical appli- cations, I conclude by suggesting conditions where resistance is likely.
Keywords: changement social; discipline; féminisme; militance; mouvements féministes; ressource en ligne; résistance; sciences humaines; sociologie; thématiques; émotions

Loving internationalism: The emotion culture of transnational women's organizations, 1888-1945 - Taylor, Verta; Rupp, Leila (Mobilization: An International Quarterly, 2002)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; allemagne; amériques; angleterre; discipline; droits des femmes*; europe; femmes* trans; france; militance; pays-bas; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis